APLIKASI GERMAN LINDUO HD SEBAGAI MEDIA PEMBELAJARAN BAHASA JERMAN KETERAMPILAN MENYIMAK KELAS XI SEMESTER I - Maghriza, Fanny; Pujosusanto, Ari (LATERNE, 2022)
Listening is one of those language skills that has a receptive or accepting nature. Students often have difficulty in understanding on foreign language listening skills. The GERMAN LINDUO HD application is present as an alternative learning media for class XI semester 1 students in adding German vocabulary to the 2013 curriculum with KD 3.2 for the die Familie theme. The formulation of the problem in this scientific article is whether the content of the GERMAN LINDUO HD application is feasible with what is in the learning media including its criteria and functions as well as the German language material for listening skills in class XI semester I. The purpose of this scientific article is to find out the feasibility of the content of the GERMAN LINDUO HD application as a medium for learning German listening skills class XI semester I based on the assessment of the results of the material expert validation test and media experts. This article uses qualitative descriptive methods. The data source is the GERMAN LINDUO HD application with the die Familie theme. Data was found in the form of 13 German vocabulary words from the die Familie theme in the GERMAN LINDUO HD application. The results of the validation test from the material expert showed that the learning media of the GERMAN LINDUO HD application got a percentage of 85%, while from the media expert it scored 86%. That means the GERMAN LINDUO HD application learning media is very feasible if it is used both material and criteria as a learning medium.